Movement detection in outdoor scenes for traffic monitoring - Liu, Yi (University of Ottawa (Canada), 2004)
One important application of image processing and computer vision is traffic monitoring and control. In this thesis, a system for detection of moving vehicles approaching an intersection from a sequence of color images acquired by a stationary camera in the context of traffic light control systems is presented. As the system is dedicated to outdoor applications, efficient and robust vehicle detection under various weather and illumination conditions is examined. To deal with these ever changing conditions, vehicle detection relies on motion segmentation and on an original algorithm using color mapping to achieve feature space segmentation. Experimental results on real outdoor sequences of images demonstrate the system's robustness under various environmental conditions.
Keywords: Engineering, System Science.